A Descriptive Study of Nurses’ Implementation of Pressure Ulcer Prevention Bundle Care in Total Care Patients - Yeni Irfiyanti; Eka Sakti Wahyuningtyas (Universitas Muhammadiyah Semarang, 2026)
Pressure ulcers are a serious health problem that serve as an indicator of hospital service quality. Proper management and prevention are important for reducing the impact and supporting infection control. If not handled appropriately and promptly, pressure ulcers can become a serious threat to patients, especially for those in total care. There is a need for an efficient and effective innovation to prevent pressure ulcers, one of which is the application of pressure ulcer prevention bundle care. This study aims to describe how well nurses implement a care bundle designed to prevent pressure ulcers in patients who require total care. This research belongs to a quantitative study with a descriptive design. The sample consisted of 34 respondents using a total sampling technique. Data analysis used univariate analysis and frequency distribution tables. The frequency distribution of respondents’ age was mostly in the adult category, with 29 respondents (85.3%). Gender was mostly in the female category with 31 respondents (91.2%). Education was mostly in the Diploma III in Nursing category, with 28 respondents (82.4%). Work experience was mostly in the category of more than 3 years, with 32 respondents (94.1%). The category of bundle care implementation for pressure ulcer prevention was mostly in the good category with 23 respondents (67.6%) and fairly good in 11 respondents (32.4%). The implementation of bundle care for pressure ulcer prevention among total care patients at RSUD Muntilan was mostly carried out well by nurses. To ensure that all nurses implement bundle care optimally, we need to improve consistency and conduct periodic evaluations.